2010
DOI: 10.1007/s11250-010-9755-3
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China

Abstract: Enzootic pneumonia caused by Mycoplasma hyopneumoniae is a severe disease of pigs, causing significant economic losses to the pig industry worldwide, including the tropical and subtropical regions. In order to obtain the baseline prevalence of M. hyopneumoniae in pigs from intensive farms in southern China, double-sandwich enzyme-linked immunosorbent assay (ELISA) was used to detect M. hyoneumoniae antibodies in 460 pig serum samples collected from 12 administrative cities in China's southern Guangdong provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…The present investigation revealed an overall 58.86% seroprevalence of M. hyopneumoniae infection in Tibetan pigs in Tibet, China, which is higher than the results of previous reports (Xing et al, 2009;Yao et al, 2010;He et al, 2011) in China of domestic pigs in low-altitude areas, and the average percentage of positive piglets is higher than in Europe (10.7%) (Villarreal et al, 2010). There are two main routes for M. hyopneumoniae to be introduced into a herd: direct transmission and airborne transmission (Batista et al, 2004).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The present investigation revealed an overall 58.86% seroprevalence of M. hyopneumoniae infection in Tibetan pigs in Tibet, China, which is higher than the results of previous reports (Xing et al, 2009;Yao et al, 2010;He et al, 2011) in China of domestic pigs in low-altitude areas, and the average percentage of positive piglets is higher than in Europe (10.7%) (Villarreal et al, 2010). There are two main routes for M. hyopneumoniae to be introduced into a herd: direct transmission and airborne transmission (Batista et al, 2004).…”
Section: Discussioncontrasting
confidence: 84%
“…Tel: +86-931-8342813. (Choi et al, 2003;Fano et al, 2005;Vengust et al, 2006;Halli et al, 2012) have been reported in many areas of the world (Choi et al, 2003;Fano et al, 2005;Vengust et al, 2006;Halli et al, 2012) including as well as many regions in China (Xing et al, 2009;Yao et al, 2010;He et al, 2011). The purpose of this survey was to investigate the seroprevalence of M. hyopneumoniae in Tibetan pigs in Tibet, China, which would provide base-line data for the prevention and control of M. hyopneumoniae infection in Tibetan pigs.…”
Section: Introductionmentioning
confidence: 99%
“…In Thailand, Damrongwatanapokin et al (2004) found 58% blood samples positive in ELISA in 22 of 23 pig breeding farms and 74.4% in 80 of 84 fattening farms. In China, among 12 intensive farms, only two of them showed no infection of M. hyoneumoniae and the seroprevalence ranged from 0% to 90%, with an average prevalence of 45.7% (He et al 2011). In Sweden, Mattsson et al (1995) detected antibodies against M. hyopneumoniae in 90% of pigs by ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Enzootic pneumonia (EP) is one of the most important sources of disease-associated losses in swine production [ 1 3 ]. This lung disease is caused by Mycoplasma hyopneumoniae (Mhyop).…”
Section: Introductionmentioning
confidence: 99%